(untitled) (Journal Intellectual Sufism Research (JISR), 2019)
The purpose of this article is to find out the description of student procrastination and the implications of counseling individuals with self-introspection techniques to overcome procrastination. This research was conducted on seventh semester Santri Achievement Scholarship Program (PBSB) students, data collection techniques were carried out by interview and observation. Subjects were 7 students and special subjects for in-depth interviews of 3 students, with the aim of deep meaning. The results of the study and discussion are that the general picture of student procrastination can be seen from postponement, laziness, and delay. While the impact of the application of self-introspection (muhasabah) by students in overcoming procrastination is to reduce procrastination, which is evident from the following indicators: first consideration before taking action, careful on activities that are priority, create better change.